Analisis Penataan Kelembagaan KP2MI dan BP2MI Ditinjau dari Asas Hukum Administrasi Negara dan Prinsip Tata Kelola Pemerintahan yang Baik - Hamler; Duwi Handoko (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Indonesian Migrant Workers (PMI) make a significant contribution to the national economy but continue to face serious challenges in terms of legal and institutional protection. The institutional transformation from BNP2TKI to BP2MI, followed by the establishment of the Ministry for the Protection of Indonesian Migrant Workers (KP2MI) through Presidential Regulation (Perpres) No. 165 of 2024, and the simultaneous reissuance of Perpres No. 166 of 2024 reinstating BP2MI, has raised concerns about overlapping functions and legal uncertainty. This study uses a normative juridical approach to analyze the institutional design compatibility of KP2MI and BP2MI with the principles of administrative law and good governance. The findings indicate a duplication of functions that contradicts the principles of legality, bureaucratic efficiency, and public accountability. Overlapping authority undermines law enforcement and weakens the overall protection of migrant workers. This study recommends a comprehensive institutional restructuring, either through the revocation of Perpres 166/2024 or amendments to both regulations with a clear delineation of functions, and the implementation of transparency, accountability, and cross-sector coordination to establish more efficient and human rights-responsive governance in the protection of Indonesian migrant workers.